Land Use Changes Analysis for Kelantan Basin Using Spatial Matrix Technique â€œPatch Analystâ€ in Relation to Flood Disaster - Syed Hussain, Tuan Pah Rokiah; Ismail, Hamidi (Journal of Techno-Social, 2011)
In the recent decade, there are many government efforts to develop rural area as a step to curb vast economic discrepancy status within community in the nation. This effort is in line with National Development Policy promoted by government shifting from New Economic Policy. Therefore, this study area also has impact done by development activities. The enormous economic developments have encourage growth in urbanization, tourism and recreation, public facilities, housing and so on. Furthermore, the area of cultivation land uses and foliages are becoming shrinking due to development growth, which is development needs to shift land use pattern hence denotes that human beings infuriate the environment to meet the life needs. In response to that, this research delves into the level of land use changes using the Geographic Information System (GIS) and Spatial Analyst to determine the actual area or vicinity and what is the type of rigorous changes in land use. This issue can be seen all the way through the study outcome via spatial analysis technique adapted from Patch Density & Size Metrics (Mean Patch Size), Edge Metrics (Total Edge (TE), Edge Density (ED), Mean Perimeter-Area Ratio (Mpar) and Shannons Diversity Index (SHDI). Results of the study show that, land use changes have occurred significantly in the study area for the period of 20 years, wher, all types of analysis verify that there is an increase in patch for every statistical test. The increase in patch is a picture of current land use changes, land use edge density and land use area in study area. Moreover, this study investigates the relationship between land use with rising flood disaster frequency and intensity variable which has always happened lately in Kelantan River Basin.